Development of an ICF‐Based Core Assessment Set for Psychiatric Occupational Therapy in Japan: A Three‐Round Delphi Study. - Kawano, Kojiro; Shiota, Shigehito; Funatsu, Kotomi; Murai, Chiga; Tamura, Takashi; Suzuki, Takaji; Higashi, Toshio; Noto, Shinichi; Hilton, Claudia (Occupational Therapy International, 2026)
Introduction: People with mental disorders have an increasing need for a comprehensive assessment tool based on the International Classification of Functioning, Disability, and Health (ICF). This study is aimed at identifying ICF categories relevant to patients with mental health in Japan using a Delphi panel of experts and provide foundational data for developing an occupational‐therapy–oriented assessment tool. Methods: A three‐round Delphi survey was conducted with a Japanese expert panel initially composed of 15 specialists (five psychiatrists, 10 occupational therapists). Questionnaires (mailed or web‐based) were developed from the ICF Checklist, existing ICF core sets, relevant clinical guidelines, and prior research. Aggregate results were submitted to participants after each round for re‐evaluation. Fourteen experts completed all rounds. Data were collected from August 2024 to January 2025. Consensus was determined according to the RAND/UCLA appropriateness method. Results: Based on consensus, 42 ICF categories were selected: 17 body functions, 21 activities and participation, and four environmental factors. The set included a relatively large proportion of activities/participation items, reflecting the emphasis of occupational therapy on engagement and participation. Agreement rates increased across rounds, indicating improving consensus and relative stability of the selected indicators. Conclusion: This Delphi study produced a preliminary ICF set applicable to patients with mental health in Japan and offers the first step toward an ICF‐based comprehensive assessment tool for occupational therapy. Future work should evaluate the reliability and validity of the extracted core set, assess its clinical utility, and incorporate perspectives of service users and families.